Frank and fearless leadership: can it survive in the 'reformed' public service - Williams, Christopher (Institute of Public Administration Australia (ACT Division), 2005)
Nearly twenty years ago the author published a paper titled, "The Concept of Bureaucratic Neutrality". This review paper re-examines the relevance of the concept, based on hind sight from the author's subsequent experience working in the highest levels of the Western Australian public service. Particular consideration is given to the relationship between ministers and senior public servants, and the nature of the advice and leadership given by public servants. In this paper, it is argued that it is increasingly difficult for senior public servants to remain 'frank and fearless' when advising ministers, because of reforms which have led to changes in the nature of the public servants' employment. The changes to the Australian public service environment over the last two decades have created many more 'occasions for fearlessness' for senior public servants.